2021
DOI: 10.1093/mnras/stab1546
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of splashback boundaries and gaseous outskirts: insights from mergers of self-similar galaxy clusters

Abstract: A self-similar spherical collapse model predicts a dark matter (DM) splashback and accretion shock in the outskirts of galaxy clusters while misses a key ingredient of structure formation – processes associated with mergers. To fill this gap, we perform simulations of merging self-similar clusters and investigate their DM and gas evolution in an idealized cosmological context. Our simulations show that the cluster rapidly contracts during the major merger and the splashback radius rsp decreases, approaching th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 110 publications
2
30
0
Order By: Relevance
“…This is a common process during structure formation, and so most shocks observed in the cluster outskirts (𝑅 1𝑅 200m ) are expected to be MA-shocks. While the origin of the MA-shock is rooted in merger events, the radial evolution of the feature -once it has been generateddepends only on smooth mass accretion (Zhang et al 2021). Finally, we stress that all of these processes detailed above are complex, highly aspherical, and vary significantly from cluster to cluster.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…This is a common process during structure formation, and so most shocks observed in the cluster outskirts (𝑅 1𝑅 200m ) are expected to be MA-shocks. While the origin of the MA-shock is rooted in merger events, the radial evolution of the feature -once it has been generateddepends only on smooth mass accretion (Zhang et al 2021). Finally, we stress that all of these processes detailed above are complex, highly aspherical, and vary significantly from cluster to cluster.…”
Section: Introductionmentioning
confidence: 92%
“…Assuming different gas adiabatic indices in the range 𝛾 ∈ [4/3, 3], and also allowing the mass accretion rate to vary, can lead to nearly factor of 2 differences in the location of the accretion shock in self-similar solutions (Shi 2016). However, more complex, 3D hydrodynamical simulations have all found that the accretion shock feature is con-sistently located well beyond the splashback radius (Paper I; Lau et al 2015;Aung et al 2020;Zhang et al 2020Zhang et al , 2021, and this is related to the MA-shocks we discussed earlier (Zhang et al 2020).…”
Section: Connecting Splashback and Shock Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet another consequence of the merger is the possibility of accelerating some of the galaxies that were initially lagging behind the NGC4839 group to the velocities higher than the group velocity (e.g. Carucci et al 2014;Zhang et al 2021). As a consequence, these galaxies might be found well ahead of the group after the first passage through the Coma core.…”
Section: Discussionmentioning
confidence: 99%